Conceptual Model for Supply Chain and Quality Management integration - Fernandes, Ana Cristina (2014)
This paper presents a conceptual model proposal for Quality Management (QM) and Supply Chain Management (SCM) integration and its impact in the companies‟ performance. Based on a literature review, a set of QM and SCM principles that promote the integration have been identified. With this model we consider that we can embrace the most important issues concerning these two organizational areas. Furthermore, the statistical validation of the proposed model and the conclusions reached could help worldwide companies to adopt new management approaches in order to improve their performance.